What do beginning students, in a rurally focused medical course, think about rural practice?. Issue 1 (December 2016) - Young, Louise; Lindsay, Daniel; Ray, Robin
Abstract Background Medical schools may select students for their attitudes towards rural medical practice, yet the rural–urban disparity in availability of medical practitioners and services has not diminished in recent times despite government initiatives and increasing numbers being trained for a career in medicine. One medical school, with a focus on rural and remote medicine, aims to select students with positive perceptions for rural medical practice. A research project collected data on the perceptions of these medical students in the first week of their medical studies. Methods Students completed a low stakes essay on the life and work of a rural doctor. Initially, this formed part of a literacy assessment to determine any students requiring remediation. All students were asked if they would consent to their essay being reviewed for a research project. Data was obtained from those students who consented and handed their essays in for review. The 103 student essays underwent thematic analysis and sentences were coded into three main themes of rural lifestyle, doctor role and rural practice. Second level themes were further elicited and results were quantified according to whether they were positive or negative. Positive themes included rural lifestyle, doctor role, views of doctor, impact on community, broader work and skills knowledge, and better relationships with community and patients. Negative themes included doctor's health, pressure on doctor, family problems, greater workload, privacy and confidentiality issues, cultural issues, isolation, limited resources and financial impacts. Quantitisation of this data was used to transform essay sentences into a numerical form which allowed statistical analysis and comparison of perceptions using Z tests. Results No significant differences on the number of positive and negative responses for rural lifestyle and rural practice were found. The rural doctor role had a significantly more positive than negative views. Significant differences were found for positive views of the rural doctor role and negative views of rural practice. Participants from a capital city background reported a significantly higher percentage of responses related to negative views of rural practice than their regional and rural counterparts. Students from capital city areas had significantly more negative views about the rural doctor role, especially related to workload, limited resources and isolation than students from rural and regional areas. Conclusion Students entering medical school already have both positive and negative views about the life and work of a rural doctor. Those students from capital city areas have significantly more negative views despite being selected to enter a medical course with a rural focus based on their expressed rural perceptions. Further work is required to refine selection criteria and the year level experiences and learning opportunities which may positively influence student perceptions about rural medical practice to overcome early negative perceptions at the beginning of medical school.